2013
DOI: 10.2340/00015555-1532
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Treatment of Adult Facial Seborrhoeic Dermatitis with 0.1% Tacrolimus Ointment: Randomized, Double-blind, Vehicle-controlled, Multi-centre Trial

Abstract: The effectiveness of intermittent topical tacrolimus to prevent relapse in patients with stabilized facial seborrhoeic dermatitis has not been evaluated. The aim of this study was to determine whether proactive use of 0.1% tacrolimus ointment can keep adult facial seborrhoeic dermatitis in remission. A total of 75 patients who had stabilized facial seborrhoeic dermatitis after 2 weeks' (open-label induction) treatment with 0.1% tacrolimus were randomized in a double-blind fashion to treatment with 0.1% tacroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The median time to first DEs was not significantly different between the two groups (mean±standard deviation: 41.17±26.41 days vs. 40.55±24.84 days; p =0.38). In the previous study, the median time to first DE of the placebo group was 18.20±9.44 days 24 . It was shown that the median time to the first DE of both groups of our study were longer than that of the placebo group of the previous study, although the maintenance period was different (20 weeks vs. 10 weeks).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The median time to first DEs was not significantly different between the two groups (mean±standard deviation: 41.17±26.41 days vs. 40.55±24.84 days; p =0.38). In the previous study, the median time to first DE of the placebo group was 18.20±9.44 days 24 . It was shown that the median time to the first DE of both groups of our study were longer than that of the placebo group of the previous study, although the maintenance period was different (20 weeks vs. 10 weeks).…”
Section: Resultsmentioning
confidence: 82%
“…4 ). In the previous study 24 , all of the 10 patients of the placebo group had DE (IGA ≥2) in 10 weeks. Eight patients of the placebo group had DE at 2 weeks, one patient at 4 weeks, and the other one patient at 6 weeks.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations